2020
DOI: 10.2147/ott.s258727
|View full text |Cite
|
Sign up to set email alerts
|

<p>lncRNA UCA1 Contributes to 5-Fluorouracil Resistance of Colorectal Cancer Cells Through miR-23b-3p/ZNF281 Axis</p>

Abstract: The chemoresistance of 5-fluorouracil (5-FU) limited the application of chemotherapy in colorectal cancer (CRC) treatment. Herein, we aimed to uncover the potential mechanism behind the 5-FU resistance of CRC cells. Methods: The abundance of long noncoding RNA urothelial carcinoma associated 1 (lncRNA UCA1), microRNA-23b-3p (miR-23b-3p) and zinc finger protein 281 (ZNF281) was measured by quantitative real-time polymerase chain reaction (qRT-PCR) in CRC tissues and cells. Western blot was conducted to examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…Furthermore, miR-23b-3p elevated 5-FU sensitivity via downregulation of ZNF281 in CRC cells, while UCA1 interference also enhanced 5-FU sensitivity. This study concluded that the UCA1/miR-23b-3p/ZNF281 axis mediates 5-FU resistance in CRC, under both in vivo and in vitro conditions [211].…”
Section: Apoptosis-related Pathwaymentioning
confidence: 74%
See 1 more Smart Citation
“…Furthermore, miR-23b-3p elevated 5-FU sensitivity via downregulation of ZNF281 in CRC cells, while UCA1 interference also enhanced 5-FU sensitivity. This study concluded that the UCA1/miR-23b-3p/ZNF281 axis mediates 5-FU resistance in CRC, under both in vivo and in vitro conditions [211].…”
Section: Apoptosis-related Pathwaymentioning
confidence: 74%
“…This work thus presented the first indications for a ceRNA network having UCA1, miR-204-5p and miR-204-5p target genes in CRC resistant cells [210]. In another study, upregulated expression of UCA1 accelerated 5-FU resistance of CRC cells by suppressing apoptosis and enhancing autophagy, via the miR-23b-3p/zinc finger protein 281 (ZNF281) axis [211]. Knockdown of miR-23b-3p reversed the inhibitory effects of UCA1 interference on 5-FU resistance by inhibiting autophagy and promoting apoptotic cell death of CRC cells.…”
Section: Apoptosis-related Pathwaymentioning
confidence: 80%
“…But, a handful of evidences discovered that lncRNAs function as crucial regulators participated in modulating inflammatory damage and influenced the pathogenesis of inflammation‐related ailments, including pneumonia 4–6 . LncRNA urothelial carcinoma‐associated 1 (UCA1) has been discovered to be closely associated with various tumors, and plays widespread role in tumorigenesis 7–9 . A large number of experiments have shown that UCA1 is related to inflammatory response which could exert proinflammatory function 10–12 .…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] LncRNA urothelial carcinoma-associated 1 (UCA1) has been discovered to be closely associated with various tumors, and plays widespread role in tumorigenesis. [7][8][9] A large number of experiments have shown that UCA1 is related to inflammatory response which could exert proinflammatory function. [10][11][12] Corroborative research disclosed that UCA1 is upregulated following LPS induced sepsis in human dermal microvascular endothelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Both classes of ncRNAs regulate multiple cellular processes such as growth, development, and differentiation showing to be crucial for cancer initiation, progression, and dissemination and can be found in serum or other body fluids bound to protein or lipid complexes, or more frequently inside extracellular vescicles (i.e., exosomes) [ 46 ]. Furthermore, these elements seem to be strongly associated with the development of drug resistance in CRC [ 47 , 48 , 49 , 50 ]. For these reasons, miRNA and lncRNAs could have potential application in diagnosis, prognosis, and treatment of CRC.…”
Section: Liquid Biopsymentioning
confidence: 99%